On the concept of diglossia - Casas Navarro, Raymundo (2003)
In this brief essay, I will elucidate the concept of diglossia from the approach of Charles Ferguson (1959) to the multiple uses it has acquired over time. The polysemy of the term in question is a clear indicator that it refers to an enormously complex reality or, indeed, to quite different realities. Indeed, the universe of diglossic relationships is so variegated that it is necessary to carry out a rigorous conceptual analysis in order to avoid falling into unpleasant confusions and unfortunate simplifications. Consequently, my main purpose is to outline the evolution of the concept to see to what extent it is still useful, especially bearing in mind the Peruvian case: what Albe1io Escobar (1979) called the language question in Peru.